Preparation and Properties of Redox-Responsive Micelles Based on Carboxylmethyl Hydroxypropyl Chitosan - Liu Jianrui; Zhang Yongqin (BIO Web of Conferences)
By employing carboxymethyl hydroxypropyl chitosan (HPCMS) as the hydrophilic unit, deoxycholic acid (DOCA) as the hydrophobic unit, and cystamine (CYS) as the linker, the synthesis involved a two-step amidation process. Initially, DOCA's carboxyl group reacted with one amino end of CYS, resulting in deoxycholic acid-cystamine (DOCA-SS-NH2). Subsequently, amidation was carried out between HPCMS's carboxyl group and the amino group of DOCA-SS-NH2, yielding the amphiphilic polymer carboxymethyl hydroxypropyl chitosan-cystamine-deoxycholic acid (HPCMS-SS-DOCA). Leveraging the self-assembly characteristics of this amphiphilic polymer, blank micelles demonstrating redox responsiveness and drugloaded micelles encapsulating doxorubicin (DOX) were formulated through dialysis. Fourier-transform infrared spectroscopy (FTIR) and proton nuclear magnetic resonance (1H NMR) were deployed to determine the chemical structures of HPCMS, DOCA-SS-NH2, and the resulting polymer HPCMS-SS-DOCA. Dynamic light scattering (DLS) and transmission electron microscopy (TEM) were utilized to examine the particle size distribution and morphology of the polymer micelles. The ultraviolet spectrophotometer assessed the drug loading and encapsulation efficiency of the drug-loaded micelles, while in vitro drug release assays investigated the redox-responsive drug release performance of the drug-loaded micelles. FTIR and 1H NMR results confirmed the successful synthesis of the amphiphilic polymer HPCMS-SS-DOCA. DLS and TEM results demonstrated that both blank and drug-loaded micelles are spherical, with small particle sizes and uniform distribution. The drug-loaded micelles exhibited an average particle size of 262.9 nm and a polydispersity index (PDI) of 0.189. The drug loading and encapsulation efficiencies were found to be 13.23% and 66.14%, respectively. In a reductive environment, in vitro drug release assays indicated that the drug release amount within 48 hours was 52.67%, while in the non-reductive environment, the drug release amount within 48 hours is only 25.57%, indicating that this polymer micelle has good redox responsiveness.